y=4(y-1)2

Simple and best practice solution for y=4(y-1)2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=4(y-1)2 equation:


Simplifying
y = 4(y + -1) * 2

Reorder the terms:
y = 4(-1 + y) * 2

Reorder the terms for easier multiplication:
y = 4 * 2(-1 + y)

Multiply 4 * 2
y = 8(-1 + y)
y = (-1 * 8 + y * 8)
y = (-8 + 8y)

Solving
y = -8 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
y + -8y = -8 + 8y + -8y

Combine like terms: y + -8y = -7y
-7y = -8 + 8y + -8y

Combine like terms: 8y + -8y = 0
-7y = -8 + 0
-7y = -8

Divide each side by '-7'.
y = 1.142857143

Simplifying
y = 1.142857143

See similar equations:

| t=3t+1 | | a^2+a-1=0 | | 2(8x-2)=6 | | 9x-3-6x=12 | | -5-9n+6= | | -3(7p+6)-2(5-20p)=3(9+6p) | | c^2=a^2+b^2 | | (n+4)*9=54 | | (n-9)*5=40 | | 13x=8x+40 | | 7(t-5)+7t=7(2t+3)-11 | | 6x=4x+10 | | 3(3x-4)=12 | | -6x^4-4x^2+2=0 | | 18+1.50n=34.50 | | (z+1)(z-12)=11(z-3) | | x^2+36-12x=0 | | 11-3x^2+7x-4=8x+1 | | 3(f+11)=-7.5-6f | | .5x-5+.5x-10=10 | | 144x^4+1152x^2-6912=0 | | 3.59-4.2=4.7a | | 4(y+3)=30 | | 5x^2+4=60 | | -3x+5=-25 | | -4+10y+12=4(2y-4)-6 | | 5x^2+4-60=0 | | 2t+9-11t+33+28=0 | | 4-6x=-44 | | p+3-5=6p-10p | | 21+16x-6x-12=109 | | 3x-2=4x+5 |

Equations solver categories